Auditor Independency as antecedents of Ethical Perception on Auditor Judgment: Study of Public Accounting Firm Auditors - Pratama, Bima Cinintya (Kompartemen : Jurnal Ilmiah Akuntansi, 2018)
This study investigates the role of auditor independency as the antecedents of the interaction effects between ethical perception towards audit judgment taken by auditors. Total samples of seventy-two auditors in public accounting firm were provided with a set of questionnaire to see their perceptions of audit judgments. The sample was conducted by convenience sampling method. Analyses of the data using Partial Least Square (PLS) method found that ethical perception and auditor independency significantly affect audit judgment taken by auditors. In addition, this study find that auditor independency can mediate the relationship between ethical perception and auditor judgment.